Discovering art. (Journal of Parents and Teachers, 2014)
Based on the needs and concerns of her students, the teachers of Early Childhood Education of San José de Valladolid begin a project based on art, painters and different pictorial techniques.
Keywords: Project Based Learning; educational experience; art; painting; painters; Childhood Education.